Anxiety Levels Are Associated with Quality of Life in Elderly People with Hypertension - Anggriani, Elsa Nala; Rahmawati, Arni Nur; Apriliyani, Ita (Poltekkes Kemenkes Aceh, 2025)
Background: Elderly people with chronic illnesses, such as hypertension, accompanied by anxiety disorders, tend to experience a reduced quality of life. This combination of physical illness and mental health issues can lead to impaired interpersonal relationships, disorientation from reality, and decreased productivity, ultimately negatively impacting their quality of life.. Purpose: To determine the relationship between anxiety levels and the quality of life of elderly people with hypertension in the Sokaraja II Community Health Center Working Area, Banyumas Regency. Methods: This research is a quantitative study with a correlational design and a cross-sectional approach. The study location covers four villages within the working area of Sokaraja II Community Health Center, Banyumas Regency. The population consisted of 470 elderly people with a history of hypertension, with a sample of 82 elderly people selected using a proportionate stratified random sampling technique. The instruments used in this study consisted of two standardized questionnaires: the Geriatric Anxiety Scale (GAS) to measure anxiety levels and the WHO Quality of Life -BREF (WHOQOL-BREF) to measure quality of life. Results: Based on the research results, the significance value of p value <0.05 with a correlation coefficient value of r = -605. The Spearman Rank test results show a p value of 0.000 where the value is <0.05, which means that there is a relationship between the level of anxiety and the quality of life of elderly people with hypertension. Conclusion: There is a negative correlation between anxiety levels and quality of life in elderly people with hypertension. The higher the anxiety level, the lower the quality of life in elderly people with hypertension.